Odpowiedzi

  • Użytkownik Zadane
2009-10-08T17:25:51+02:00

y=-3x²+2x+1
Liczymy Δ=2²-4*(-3)*1=4+12=16, zatem √Δ=±4 więc
x₁=[-2-4]/(-6)=(-6)/(-6)=1
x₂=[-2+4]/(-6)=2/(-6)=-1/3
Zatem y=-3x²+2x+1=-3(x-1)(x+(1/3))

y=x²+x√2-4
Liczymy Δ=(√2)²-4*(-4)*1=2+16=18, zatem √Δ=√18=√(9*2)=3√2 więc
x₁=[-√2-3√2]/2=-4√2/2=-2√2
x₂=[-√2+3√2]/2=2√2/2=√2
Zatem y=x²+x√2-4=(x-√2)(x+2√2)

Zapisz w postaci kanonicznej:
y=x²+4x+5=(x+2)²-4+5=(x+2)²+1
lub liczymy współrzędne wierzchołków i wstawiamy do wzoru
p=(-b)/2a=-4/2=-2
q=-Δ/4a=4/4=1
Δ=4²-4*1*5=16-20=-4
y=a(x-p)²+q
y=(x+2)²+1

y=x²-3x-7 =(x-(3/2))²-9/4-7=(x-(3/2))²-(9 i 1/4)
lub liczymy współrzędne wierzchołków i wstawiamy do wzoru
p=(-b)/2a=3/2=3/2
q=-Δ/4a=-37/4=-37/4=-(9 i 1/4)
Δ=(-3)²-4*1*(-7)=9+28=37
y=a(x-p)²+q
y=(x-(3/2))²-(9 i 1/4)